Self-Introspection as an Idea in Creating Paintings - Kepakisan, Gede Agung Nugraha Arya; Yudha, I Made Bendi; Kondra, I Wayan (Program Studi Seni Murni ISI Bali, 2024)
This thesis contains a description of the creation of works of painting with the theme